2390. Avibactam Sensitizes NDM Klebsiella pneumoniae to Innate Immune Killing by Human Cathelicidin LL-37, Serum, Neutrophils, and Platelets. (26th November 2018) - Ulloa, Erlinda Rose; Dillon, Nicholas; Sakoulas, George; Nizet, Victor
Abstract: Background: Avibactam (AVI) is a broad-spectrum intravenous non-β-lactam/β-lactamase inhibitor with no reported activity against metallo-β-lactamases such as New Delhi metallo-β-lactamases (NDM). Structural similarities between β-lactamases and bacterial penicillin-binding proteins (PBPs) have led investigators to explore and confirm the hypothesis that AVI may interact with PBPs of several Gram-negative and -positive bacterial species. Potent synergy has also been observed between AVI and peptide antibiotics such as polymyxin B. We hypothesized that sub-bacteriostatic concentrations of AVI may bind PBPs to weaken cell wall integrity and enhance lysis by the membrane attack complex of complement and by endogenous cationic antimicrobial peptides (AMPs) such as human cathelicidin LL-37. Sensitization to endogenous AMPs could improve killing by neutrophils and platelets that release these effectors upon degranulation. Methods: Using NDM K. pneumoniae (NDM-KP) as a model, we performed LL-37 kill curves and killing assays with human serum, neutrophils and platelets in the presence or absence of AVI 4 μg/mL against NDM-KP. Results: AVI alone lacked in vitro activity against NDM-KP. Addition of AVI to a physiological achievable concentration of LL-37 (2 mM) was bactericidal and resulted in an 8-log10 reduction (below detection limit) in recoverable NDM-KP CFU at 6 and 24 h; no bactericidal activity was seen in bacteria treated with LL-37 or AVI alone ( P < 0.0001). AVI pretreatment dramatically sensitized NDM-KP to neutrophil and platelet killing ( P < 0.0001 and P < 0.01, respectively). AVI also sensitized NDM-KP to 20% human serum, resulting in 8-log10 reduction in recoverable NDM-KP CFU within 6 h ( P < 0.0001), an effect abrogated by heat treatment to inactivate complement. Conclusion: AVI demonstrates potent synergy with peptide antibiotics and the innate immune system in vitro . Since AVI alone has scant direct antimicrobial activity and no direct inhibitory effect on metallo-β-lactamases, it is less likely to increase selective pressures toward antibiotic resistance. The use of AVI in combination with other antibiotics against drug-resistant bacterial pathogens warrants further study. Disclosures: G. Sakoulas, Allergan: Consultant and Speaker, Consulting fee and Speaker honorarium. Sunovion: Speaker, Speaker honorarium. The Medicines Company: Speaker, Consulting fee. Paratek Pharmaceuticals: Consultant, Consulting fee. Cidara Therapeutics: Scientific Advisor, None. Arsanis Pharmaceuticals: Scientific Advisor, None.